Inovasi Jaringan Pelayanan Bagi Penyandang Disabilitas (Jalan Pintas) di Dinas Kependudukan dan Pencatatan Sipil, Kabupaten Pasuruan - Riberu, Maria Gabriella; Wulandary, Roro Merry Chornelia; Ra'is, Dekki Umamur (Indonesian Social Science Review, 2024)
Administrative services in Indonesia are still an issue that needs comprehensive attention and resolution. There is still discrimination in public service practices for vulnerable groups of persons with disabilities. Therefore, public service providers must be based on social justice without discriminatory elements. As stated in Law Number 25 of 2009 concerning public services which is a breath of fresh air in efforts to provide good public services. So innovation is needed which is the main need as an answer to the various problems that are being faced. This study aims to find out the innovation of "Jalan Pintas" in the Pasuruan Regency Population and Civil Registration Office and what are the factors that influence the innovation of "Shortcuts".  This research method uses qualitative methods. The data collection techniques used are interviews, observation, and documentation. The informant determination technique is purposive sampling, namely the head of the information management division of the population administration and the community with disabilities. The results of the researcher's research show that this innovation is seen from the advantages, suitability, complexity, possibility of being tried and then observed to obtain the results that this innovation makes it easier for people with disabilities to fulfill population documents for people who have physical and mental limitations. The results in this Shortcut innovation service are in the form of Biodata, KK, and KTP-El. As for the supporting factors, namely the laws that regulate and facilities and infrastructure. And the inhibiting factor is the awareness of people with disabilities on the importance of population documents and network constraints during services. Pelayanan administrasi di Indonesia masih menjadi persoalan yang perlu memperoleh perhatian dan penyelesaian yang komperhensif. Masih ada diskriminasi dalam praktik pelayanan publik bagi kelompok rentan penyandang disabilitas. Maka dari itu penyelenggara pelayanan publik harus berasaskan keadilan sosial tanpa unsur diskriminatif. Seperti yang tertera dalam Undang-Undang Nomor 25 Tahun 2009 tentang pelayanan publik yang menjadi angin segar dalam upaya peneyedian pelayanan publik yang baik. Maka diperlukan inovasi yang menjadi kebutuhan utama sebagai jawaban atas beragam persoalan yang tengah dihadapi. Penelitian ini memiliki tujuan untuk mengetahui inovasi “Jalan Pintas” di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Pasuruan dan apa saja faktor yang mempengaruhi inovasi “Jalan Pintas”.  Metode penelitian ini menggunakan metode kualitatif. Teknik pengumpulan data yang digunakan adalah wawancara, observasi, dan dokumentasi. Teknik penentuan informan adalah purposive sampling yaitu kepala bidang pengelolaan informasi administrasi kependudukan dan masyarakat penyandang disabilitas. Hasil penelitian peneliti menunjukan bahwa Inovasi ini dilihat dari keuntungan, kesesuaian, kerumitan, kemungkinan dicoba dan kemudian diamati memperoleh hasil bahwa inovasi ini memudahkan masyarakat penyandang disabilitas dalam memenuhi dokumen kependudukan bagi masyarakat yang mempunyai keterbatasan fisik dan mental. Hasil dalam pelayanan inovasi Jalan Pintas ini berupa Biodata, KK, dan KTP-El. Sedangkan untuk faktor pendukung yaitu Undang-Undang yang mengatur serta sarana dan prasarana. Dan faktor penghambat yaitu kesadaran masyarakat penyandang disabilitas terhadap pentingnya dokumen kependudukan dan kendala jaringan saat pelayanan